Caprine Endometrial Mesenchymal Stromal Stem Cell: Multilineage Potential, Characterization, and Growth Kinetics in Breeding and Anestrous Stages. (5th March 2017) - Tamadon, Amin; Mehrabani, Davood; Zarezadeh, Younes; Rahmanifar, Farhad; Dianatpour, Mehdi; Zare, Shahrokh
Abstract : The endometrial layer of the uterus contains a population of cells with similar characteristics of mesenchymal stem cells (MSCs). In the present study, caprine endometrial mesenchymal stromal stem cells (En-MSCs) characters and differentiation potential to chondrogenic, osteogenic, and adipogenic cell lines as well as their growth kinetics in breeding and anestrous stages were evaluated. En-MSCs were enzymatically isolated from endometrial layer of the uterus of adult goats and were cultured and subcultured until passage 4. The growth kinetics and population doubling time (PDT) of caprine En-MSCs in breeding and anestrous stages were determined. En-MSCs in passage 4 were used for the karyotyping and differentiation into chondrocytes, osteocytes, and adipocytes. The PDT in anestrus phase was 40.6 h and in cyclic goats was 53 h. En-MSCs were fibroblast-like in all passages. The number of chromosomes was normal (2 n = 60 ) with no chromosomal instability. Chondrogenic, osteogenic, and adipogenic differentiation of En-MSCs was confirmed by staining with Alcian blue, Alizarin red, and Oil Red O, respectively. Caprine En-MSCs demonstrated to be an alternative source of MSCs for cell therapy purposes in regenerative medicine.